Evaluating the efficacy of metal suction cannula for atonic postpartum haemorrhage management in rural south Gujarat: a two-year observational study - Shrivastav, Ritika; Shrivastava, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In resource-constrained regions characterized by limited healthcare infrastructure, low female literacy rates, and constrained access to medical resources, postpartum hemorrhage (PPH) remains a dire obstetric emergency. This research article investigates the effectiveness of metal suction cannula as a simple, safe and cost-effective technique for atonic PPH management in a private hospital in Rural South Gujarat. The primary aim of this study was to examine the effectiveness of the metal suction cannula in managing atonic PPH and the maternal outcome after suction technique. Methods: This observational study was conducted in Shreeji hospital, a private multifacility hospital in rural south Gujarat over the period of two years, between June 2021-May 2023 and involved 148 patients who were admitted for labour and delivery but later developed atonic PPH after AMTSL. Metal cannula and high vacuum suction machine was used. Data like patient demographics, risk factors, and post-procedural outcomes were studied. Results: Following application of the metal vacuum cannula technique, bleeding stopped within five minutes in 78 women (52.7%). For 53 women (35.8%), bleeding ceased between 5-10 minutes. In 17 women (11.4%), bleeding was effectively halted after more than ten minutes. In 87 women (58.8%), negative pressure was applied only once, resulting in successful hemorrhage control. 38 women (25.6%) required suction application two times and 25 women (20.8%) needed three applications of negative pressure to effectively stop the bleeding. The volume of blood collected in the bottle after metal vacuum cannula application ranged from 100 to 300 ml. Conclusions: Factors such as ease of use, affordability, and improved clinical outcomes make suction cannulas an effective tool in the management of PPH in resource limited areas. It requires minimal training, conserves the uterus, is technically less challenging and reduces the requirement of blood and blood products.